Effect of Wolffia Meal [Wolffia globosa (L). Wimm.] As a Dietary Protein Replacement on Performance and Carcass Characteristics in Broilers - Chantiratikul, A.; Pooponpan, P.; Santhaweesuk, S.; Chantiratikul, P.; Sangdee, A.; Maneechote, U.; Bunchasak, C.; Chinrasri, O. (International Journal of Poultry Science, 2010)
Crude Protein (CP) from Wolffia meal [Wolffia globosa (L). Wimm.] was used to replace CP from Soybean Meal (SBM) in the diets of broilers to determine its effect on the broiler’s productive performance and carcass characteristics. Using Completely Randomize Design, 384 ten-day-old broilers were divided into 4 treatments; each treatment consisted of 3 replicates of 16 birds each. The treatments were T1: control diet, T2, T3 and T4: 25, 50 and 75% of CP from SBM was replaced by CP from Wolffia meal, respectively. The results indicated that feed intake, average daily gain, feed conversion ratio, protein efficiency ratio and carcass characteristics of control group were better (p